Surah Al-Nur: Ditinjau Dari Potret Estetika Dan Ilustrasi Artistik Bahasa - Siti Maisaroh (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2017)
Al-Qur’an owning many idiosyncrasy, not only guidance moslem people life, on the other side, language of Al-Qur’an also invite astonishment manner for all human being, moslem and also non moslem. In this case, researcher will study al-Nur Surah and all language idiosyncrasy in it. This research is aimed at: 1. To know any kind of language esthetic side evaluated from science of Arabic language rhetorica (ilm al-Balaghah) in al-Nur Surah 2. To know how language artistic illustration in al-Nur. The design of this research is qualitative research which is use a descriptive analysis Approach and with reference triangulation method, that is a style try to show message from Al-Qur’an as alive message, present and concrete can make comprehension for the reciter and give hard motivation to practice the holy message contained inside Al-qur’an. The subjects were the sentences in al-Nur which representing to 24 of Al-Qur’an Surah. Al-Nur which discussing many moral social of society and arrange the social order of society by usage beauty of Arabic Ianguage from Ianguage illustrative, esthetics value and the beauty of very high rhetoric Ianguage which has no equal in this world. So that this Ianguage easy to touched being soul and logic and be especial reference in take of law and mannage pattern live society.